Prospects for eradication of meningococcal disease. Issue 11 (15th September 2012) - Nadel, Simon
Abstract : Meningococcal meningitis and septicaemia remain a serious global health threat. This review focuses on the epidemiology of meningococcal disease following the recent implementation of effective vaccines and the potential utility of a vaccine against serogroup B meningococcus.